(untitled) (Global Journal of Human-Social Science, 2023)
In this article I present historical data about the creation of the city of Mariana located in the state of Minas Gerais Brazil This city was of great importance throughout the 18th and 19th centuries as it housed authorities and political religious and administrative institutions The information presented in the article was gathered through extensive bibliographical and documental research carried out from the approach of Social History and Italian micro-history In the records about the construction of the city the efforts of the authorities to order the public spaces were noted guaranteeing the control of material goods and the movement of people through the territory of the mines